Legal Protection For Buyers When The Seller’s Party Is Unknow In The Transfer Of Land Rights (Study Of Decision Number 20/Pdt.G/2023/PN Tgt) - Anarki Soffanda, Cikal; Purwaningsih, Prihatini (Universitas Ibn Khaldun Bogor, 2025)
This research is motivated by the large number of perpetrators of human trafficking crimes committed by prostitution in contract marriages, this incident was carried out in Puncak Cisarua Bogor between Foreign Citizens and Indonesian Citizens. This is done in order to gain benefits for both the victim and the perpetrator, the results of which will be divided in two, this action is often carried out by someone either for primary income or additional income. This study aims to determine how the law is enforced for the crime of human trafficking in contract marriages and how the judge's decision is considered against the crime of human trafficking in contract marriages. This study uses a qualitative method, namely based on data obtained and reviewed systematically, systematically and statistically based on data that has been obtained from the decision. In the trial process, evidence, facts and everything related to the case of human trafficking in contract marriages will be tested with the aim of determining how someone is motivated to commit the act and how the law is enforced and whether the perpetrator receives a commensurate punishment in accordance with Law of the Republic of Indonesia No. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. Based on the results of the research in the case study, the verdict shows that the defendant O. Nurmalasari Alias Ebeh Alias Enur Binti Ahmad is guilty of committing the crime of human trafficking as stated in the provisions of Article 2 Paragraph (1) and (2) of Law No. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. Therefore, the results of the verdict state that the perpetrator is proven guilty and is sentenced to a criminal penalty of 4 (four) years in prison with a fine of Rp. 150,000,000 (One Hundred and Fifty Million Rupiah) subsidiary to 4 (four) months in prison.